Selective prevention of cardiovascular disease using integrated lifestyle intervention in primary care: protocol of the Healthy Heart stepped-wedge trial - Mattijs E Numans; Tobias N Bonten; Niels H Chavannes; Wilbert B van den Hout; Rianne MJJ van der Kleij; Sanne Marije Verkleij; Karin Busch (BMJ Open, 2021)
Introduction Lifestyle interventions are shown to be effective in improving cardiovascular disease (CVD) risk factors. It has been suggested that general practitioners can play an essential role in CVD prevention. However, studies into lifestyle interventions for primary care patients at high cardiovascular risk are scarce and structural implementation of lifestyle interventions can be challenging. Therefore, this study aims to (1) evaluate (cost-)effectiveness of implementation of an integrated group-based lifestyle programme in primary care practices; (2) identify effective intervention elements and (3) identify implementation determinants of an integrated group-based lifestyle intervention for patients with high cardiovascular risk.Methods and analysis The Healthy Heart study is a non-randomised cluster stepped-wedge trial. Primary care practices will first offer standard care during a control period of 2–6 months, after which practices will switch (step) to the intervention, offering participants a choice between a group-based lifestyle programme or standard care. Participants enrolled during the control period (standard care) will be compared with participants enrolled during the intervention period (combined standard care and group-based lifestyle intervention). We aim to include 1600 primary care patients with high cardiovascular risk from 55 primary care practices in the area of The Hague, the Netherlands. A mixed-methods process evaluation will be used to simultaneously assess effectiveness and implementation outcomes. The primary outcome measure will be achievement of individual lifestyle goals after 6 months. Secondary outcomes include lifestyle change of five lifestyle components (smoking, alcohol consumption, diet, weight and physical activity) and improvement of quality of life and self-efficacy. Outcomes are assessed using validated questionnaires at baseline and 3, 6, 12 and 24 months of follow-up. Routine care data will be used to compare blood pressure and cholesterol levels. Cost-effectiveness of the lifestyle intervention will be evaluated. Implementation outcomes will be assessed using the RE-AIM model, to assesses five dimensions of implementation at different levels of organisation: reach, efficacy, adoption, implementation and maintenance. Determinants of adoption and implementation will be assessed using focus groups consisting of professionals and patients.Ethics and dissemination This study is approved by the Ethics Committee of the Leiden University Medical Center (P17.079). Results will be shared with the primary care group, healthcare providers and patients, and will be disseminated through journal publications and conference presentations.Trial registration number NL60795.058.17. Status: pre-results